Synthesis of Heterasumanene - Li, Xuexiang; Shao, Xiangfeng (Synlett, 2014)
This article outlines the efforts toward the synthesis of heterasumanene, a buckybowl consisting of four six-membered and three five-membered rings. Special attention is paid to our achievement on the facile and large-scale synthesis of trithia- and triselenasumanenes.
Keywords: polycycles; buckybowls; sulfur; selenium; silicon